SISTEM INFORMASI KLINIK PERSATUAN PEMBERANTASAN TUBERKULOSIS INDONESIA (PPTI) WILAYAH JAMBI - Elzas -; Puput Patmawati (JURNAL AKADEMIKA)
Clinical information systems Indonesian Tuberculosis Eradication Association (PPTI) Region Jambi is a system that displays information about Clinical Indonesian Tuberculosis Eradication Association (PPTI) Jambi region that use the Website may be better, because there is an information system in the clinic Indonesian Tuberculosis Eradication Association (PPTI ) Jambi region.